High prevalence of deleterious variants in cardiomyopathy genes in patients with early onset atrial fibrillation. (3rd October 2022) - Vad, O B; Ahlberg, G; Paludan-Muller, C; Refsgaard, L; Sajadieh, A; Haunsoe, S; Bundgaard, H; Svendsen, J H; Olesen, M S
Abstract: Background: Atrial Fibrillation (AF) is a common cardiac arrhythmia associated with increased morbidity and mortality. AF has a significant heritable component and genome-wide association studies have associated numerous loci in the human genome with AF. The arrhythmia is relatively rare in younger individuals, but studies have shown that individuals with early-onset AF may harbour a considerable burden of pathogenic genetic variants. In recent years, the concept of atrial cardiomyopathy has emerged as a mechanism involved in AF pathogenesis. Genes well-known to be related to ventricular structure, including cardiomyopathies have now also been associated with AF. Purpose: Using targeted genetic sequencing, this study aimed to elucidate the role of deleterious genetic variants in cardiomyopathy genes in early-onset AF, and provide new insights into AF pathogenesis. Methods: We performed targeted genetic sequencing of 445 Danish individuals with onset of AF before age 40 years and no other cardiovascular co-morbidities, and of 387 controls with no history of AF. Based on guidelines for genetic testing for clinical use, we focused on 30 genes with well-established associations with dilated cardiomyopathy, hypertrophic cardiomyopathy and arrhythmogenic right ventricular cardiomyopathy. We examined the prevalence of loss-of-function variants (defined as variants leading to premature stop-codon, frameshift or splice-site variants), as these are most likely to be disease-causing. We filtered for rare variants using a minor allele frequency <0.1%. The difference in prevalence in the two groups was analyzed using a logistic regression model. Results: We found that 38 of the 445 early-onset AF patients carried loss-of-function variants in well-established cardiomyopathy genes. The prevalence of rare, loss-of-function variants was enriched in cases compared with controls (8.5%. vs. 1.0%, P=8.27x10 –7 ). The variants were identified in eight different genes, with most rare variants found in the TTN gene (Table 1). In sensitivity analyses excluding TTN variants, we found that 12 individuals (∼2.7%) with AF harbored deleterious loss-of-function variants (P=0.0396). Conclusions: Individuals with early onset of AF have a considerable burden of rare, deleterious variants in established cardiomyopathy genes. These new insights could help inform future recommendations for genetic testing and follow-up to detect early cardiomyopathy manifestations to prevent adverse outcomes in patients with early onset of AF. These findings support the presence of atrial cardiomyopathy. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Hallas-Møller emerging investigator grant, The Novo Nordisk Foundation (NNF: NNF17OC0031204)The John and Birthe Meyer Foundation